2016
DOI: 10.18312/1980-7341.n15.2016.343
|View full text |Cite
|
Sign up to set email alerts
|

Apneia Do Sono E Obesidade: Revisão De Literatura

Abstract: A apneia é a interrupção completa do fluxo de ar nas vias aéreas superiores, com despertares curtos durante o sono. Isso ocasiona a falta de ventilação alveolar resultando em dessaturação da oxihemoglobina e aumento da pressão parcial de gás carbônico no sangue arterial (PaCO2). O presente artigo descreve a fisiopatologia, os fatores de risco, o diagnóstico e o tratamento da apneia, com destaque para uma das principais comorbidades: a obesidade. Este artigo busca reconhecer a importância do conhecimento da apn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…However, a generic interpretation of the findings in this study points that greater concentration of fat, greater BMI and low body water concentration (tissue dehydration) negatively impacted sleep quality, specifically on sleep disturbances, customary sleep efficiency and sleep duration. Although no studies, with similar methodological profile, were found demonstrating such correlations, other studies demonstrated general causal relation between increased body fat and impaired sleep (Carvalho et al 2015;Lustosa et al 2016;Monçale Neto et al 2016;Ruthes et al 2017;Zimberg et al 2017;Andrade et al 2018;Cardoso and Chagas 2019;Heath et al 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a generic interpretation of the findings in this study points that greater concentration of fat, greater BMI and low body water concentration (tissue dehydration) negatively impacted sleep quality, specifically on sleep disturbances, customary sleep efficiency and sleep duration. Although no studies, with similar methodological profile, were found demonstrating such correlations, other studies demonstrated general causal relation between increased body fat and impaired sleep (Carvalho et al 2015;Lustosa et al 2016;Monçale Neto et al 2016;Ruthes et al 2017;Zimberg et al 2017;Andrade et al 2018;Cardoso and Chagas 2019;Heath et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Attention must be drawn to the relation between greater likelihood to work difficulties and occupational accidents with persons presenting sleep disturbances (Monçale Neto et al 2016). For this reason, the need of tools optimizing sleep quality and life quality of nursing and health professionals has been frequently emphasized in order to reduce iatrogenic situations.…”
Section: Discussionmentioning
confidence: 99%